(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In today’s conditions, as the lighting system improves and the consumption of light diodes, which consume less energy instead of incandescent lamps, increases, the demand for thermoelectric generators is increasing again.